2017
DOI: 10.1002/cphc.201700848
|View full text |Cite
|
Sign up to set email alerts
|

Inversion of Bicyclic Decanes: Rotational Spectra of the Trans and Double Cis Conformations of 2‐Decalone

Abstract: The conformational landscape of the bicyclic molecule 2-decalone has been studied in a jet-cooled expansion by using rotational spectroscopy. The investigation covered the frequency region 7-19 GHz using broadband fast-passage IMPACT Fourier-transform microwave techniques. The introduction of the asymmetric carbonyl substituent in the double-chair decalin skeleton originates two distinct inverting conformers with cis ring junction, which were independently identified and characterized in the gas phase. Additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…High‐resolution rotational spectroscopy provides a stringent probe of molecular structures because already small structural changes lead to clear differences in the rotational spectrum. It can be used to unambiguously identify the low energy conformers present in the cold environment of a supersonic jet and to determine the energy order by their intensities, as demonstrated in the present work. This study is also important to further evaluate the applicability of rotational spectroscopy to larger molecular systems .…”
Section: Figurementioning
confidence: 89%
“…High‐resolution rotational spectroscopy provides a stringent probe of molecular structures because already small structural changes lead to clear differences in the rotational spectrum. It can be used to unambiguously identify the low energy conformers present in the cold environment of a supersonic jet and to determine the energy order by their intensities, as demonstrated in the present work. This study is also important to further evaluate the applicability of rotational spectroscopy to larger molecular systems .…”
Section: Figurementioning
confidence: 89%
“… a Experimental ground state rotational constants (taken from refs for pyrazole, halogenated pyrazoles, cyclobutenone, cyclopentanone, t-2-decalone, imidazole, indole, fluorene, and 1-methyl-1 H -cyclopenta­[ a ]­naphthalene, respectively) rounded to one decimal place. b 1-Methyl-1 H -cyclopenta­[ a ]­naphthalene. …”
Section: Resultsmentioning
confidence: 99%
“…It is quite apparent that the PCSB model reaches the 0.1% target for halogen-substituted heteroaromatics (Br- and I-pyrazole), molecules experiencing significant strain (cyclobutenone) or involving large saturated cycles (t-2-decalone), and typical building blocks of biomolecules (cyclopentanone, pyrazole, imidazole, and indole) or molecular motors (fluorene and 1-methyl-1 H -cyclopenta­[ a ]­naphthalene). Taking into account also the results of previous studies, , it can be concluded that the structures of semirigid molecules containing up to about 20 atoms are described accurately at DFT cost.…”
Section: Resultsmentioning
confidence: 99%
“…Our work follows previous rotational investigations of other quinolizidine alkaloids such as sparteine 26 and lupinine, 27 tropane 28,29 and norbornane 30 bicycles, and related derivatives. 31…”
Section: ■ Introductionmentioning
confidence: 99%
“…The high resolution (∼10 –7 cm –1 ) of rotational spectra is critically sensitive to the molecular structure, precisely resolving all populated species and offering the most accurate description of the intrinsic structural properties and plausible conformational equilibria in matrine. Our work follows previous rotational investigations of other quinolizidine alkaloids such as sparteine and lupinine, tropane , and norbornane bicycles, and related derivatives …”
Section: Introductionmentioning
confidence: 99%